Localizing National Issue as a Campaign Strategy in West Java Governor Election 2018 - Muryanto Amin; Alwi Dahlan Ritonga; Muradi Muradi (Humanus: Jurnal Ilmiah Ilmu-ilmu Humaniora, 2021)
West Java becomes one of central attention in the governor election in 2018. This article attempts to depict how the strategy of the governor candidate pair Sudrajat-Akhmad Syaikhu (henceforth ASYIK) in gaining the votes in the local leader election. This study used a documentation method with a type of descriptive analysis. The data were taken from online media including Liputan6.com, Detik.com, Pikiran-Rakyat.com, and Republika.com. It was found that the ASYIK candidate pair used campaign strategy by localizing national issues so that it could increase the electability and gain a large number of votes on election day. Unexpectedly, by using this strategy, they could get second place with the most votes. Whereas, previously, from the findings of several survey institutions, the ASYIK pair was predicted to be in the third position with a large gap of electability and popularity behind the top two pairs. But, after final counting and recapitulation of the election that was held on 27th June 2018, ASYIK ranked in the top two after overtaking the pair of Dedy Mizwar – Dedy Mulyadi.